TeleParallax: Low-Motion-Blur Stereoscopic System With Correct Interpupillary Distance for 3D Head Rotations - Amemiya, Tomohiro; Aoyama, Kazuma; Hirose, Michitaka (Frontiers in Virtual Reality, 2021)
Binocular parallax provides cues for depth information when a scene is viewed with both eyes. In visual telepresence systems, stereo cameras are commonly used to simulate human eyes. However, motion blur occurs when these cameras are rotated quickly. The use of omnidirectional cameras can reduce the motion blur, but does not provide the correct interpupillary distance (IPD) when viewers tilt or turn their heads sideways. We propose a method called TeleParallax, in which two omnidirectional cameras are separated by the IPD and the direction of the lenses are kept constant in world coordinates by robotic arms during three-dimensional head rotations. TeleParallax can suppress the increase in image buffer during head rotations because each camera can capture an omnidirectional image with the lens direction fixed. We conducted three user studies to evaluate the perceptual effect of head tilt, eye asynchrony, and delays in IPD correction for a particular rotation. The results indicate that TeleParallax can provide depth perception that is independent of the head movement with less visual discomfort. Although the results show that the users were sensitive to the asynchrony between their eyes and to camera motion during IPDs, they retained the feeling of depth perception within interocular delays of 70 ms and motion velocity of 75 degrees/s. These results imply that TeleParallax has remarkable potential for visual telepresence systems.